Republic of Palau : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper describes Palau's fiscal challenges and policy options to achieve long-term fiscal sustainability. Palau relies heavily on compact grants, and without continued fiscal consolidation over the medium term, the fiscal position will become unsustainable after these grants expire in FY2024. The fiscal sustainability analysis uses an intertemporal budget constraint model to show that reducing the current deficit excluding grants by about 8 percentage points of GDP during FY2014-19 would ensure Palau's long-term fiscal sustainability. The paper also discusses the role of tourism in Palau and identifies policy priorities to further promote this sector and sustain growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet